2022
DOI: 10.3390/ijerph19031445
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impacts of COVID-19 Pandemic among Emerging Adults: An Observational Cross-Sectional Study

Abstract: (1) Background: COVID-19 has had psychological impacts, particularly anxiety, depression, anger, and suicidal ideation, on the world’s populace, including young persons who were prone to mental health disorders even before the pandemic. We described the psychological impacts of COVID-19 among emerging adults aged 18–30 years in Saudi Arabia. (2) Methods: A cross-sectional survey was done among a randomly sampled population in Saudi Arabia between July 2020 and May 2021 using the DSM-5 Self-rated Level 1 Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…New limitations on daily life and social activities within an unknown process will cause a population to suffer from stress and worry and as a result, confidence may be lost among survivors and the mental health of the society negatively affected [37]. In the recent literature, it is possible to come across studies suggesting that timely handling of mental health burdens by using simple, self-administered screening tools will prevent dire consequences in the future [38]. The most recent studies on adolescents in the literature were reviewed and it was found that 20% of the adolescents experienced psychological trauma symptoms during the COVID-19 epidemic; It was emphasized that there is a critical need to provide mental health services such as school-based services to adolescents to reduce the longterm negative psychological impact of the pandemic [39].…”
Section: Discussionmentioning
confidence: 99%
“…New limitations on daily life and social activities within an unknown process will cause a population to suffer from stress and worry and as a result, confidence may be lost among survivors and the mental health of the society negatively affected [37]. In the recent literature, it is possible to come across studies suggesting that timely handling of mental health burdens by using simple, self-administered screening tools will prevent dire consequences in the future [38]. The most recent studies on adolescents in the literature were reviewed and it was found that 20% of the adolescents experienced psychological trauma symptoms during the COVID-19 epidemic; It was emphasized that there is a critical need to provide mental health services such as school-based services to adolescents to reduce the longterm negative psychological impact of the pandemic [39].…”
Section: Discussionmentioning
confidence: 99%
“…As early as February 2020, psychiatrists and researchers were warning of the impact of lockdowns and other responses on depression, anxiety, fear, panic attacks, suicidality, and other severe mental health problems, among both patients and health workers [ 43 , 44 ]. Studies around the world have found alarming rates of depression and stress on particular groups, such as caregivers of persons with dementia in Hong Kong (nearly two-thirds suffered from probable depression) [ 45 ], college students in Poland (over one-third reported poor mental health requiring treatment) [ 46 ], college students in China (nearly one-quarter reported mild-to-severe anxiety) [ 47 ], and young adults in Saudi Arabia (over 90% reported mild-to-severe symptoms of mental health disease) [ 48 ].…”
Section: Covid-19 Pandemic Responsementioning
confidence: 99%
“…Among the numerous studies on the impact of COVID-19 on adolescent mental health, existing studies tend to collect data during the epidemic period and conduct cross-sectional studies to study the impact of COVID-19 on adolescent mental health from the aspects of isolation, social support, positive and negative emotions towards COVID-19 during the pandemic (6,14,(16)(17)(18). There are some obvious limitations to these studies.…”
Section: Introductionmentioning
confidence: 99%